Comparison of impression techniques and double pouring by dental cast's accuracy. Preliminary clinical-lab trial - Messias, Aion Mangino [UNESP]; Silva, Stephania Caroline Rodolfo [UNESP]; Abi-Rached, Filipe de Oliveira [UNESP]; Souza, Raphael de Freitas; Reis, José Maurício Dos Santos Nunes [UNESP] (Universidade Estadual de Campinas, 2019)
Aim: This study compared impression techniques and double pouring by means of cast's accuracy. Methods: For each patient (n=10), impressions from right maxillary canine to first molar were made with acrylic resin trays and vinyl-polysiloxane using one single-step, and four two-steps techniques: relief with poly(vinyl chloride) film; tungstencarbide bur/scalpel blade; small movements of the tray; non-relief. Total visible buccal surface area of crowns was measured three times using photographs from patients (Baseline) and casts. Mean area values (mm2) between Baseline and casts differences were analyzed by two-way repeated-measures ANOVA (α=.05; 1-β=85%). Results: No significant differences were observed for Impression Techniques (P=.525), Double Pouring (P=.281), and their interaction (P=.809). Conclusion: All impression techniques and double pouring produced casts with similar accuracy.
Keywords: Dental; Dental impression materials; Dental impression technique; Dimensional measurement accuracy; Photography